Trabalho objetivado: a crítica da macroeconomia do FMI - 1980-2008 - uma contribuição ao debate - Neves Filho, Albério (2012)
Following doctoral thesis developed in terms of qualification project of post-graduate studies program in social sciences from the Pontifícia Universidade Católica de São Paulo. The goal of the thesis presented here is to examine the political assumptions expressed in macroeconomic models of the International Monetary Fund adjustment and the political conditions necessary for its implementation, in the period 1980-2008. And justifications to develop a work of this nature were provided both by the recognized critical social and economic effects, as the current theoretical controversies existing on the pertinence of such programs and the reasons that led the IMF to promote macroeconomic policy, contained therein. The hypothesis explored here is that macroeconomic adjustment programmes developed and deployed by the IMF, indifferently applied in the various national economies and after the period of the so-called debt crisis, sought to make and was a result of complying with regulatory rules and symbolic imposed at the time and throughout the period in which gives the ownership of real resources in the Central States, by class of bankers. From this point of view, this change produced a rearrangement within the economic and political theories in use by the Fund, implying several attempts on your part, to the economic reconstruction of the most basic postulates, which formed the action parameter to the institution, in the long period from after World War II. The theoretical-methodological aspects are developed here, first, use of the postulates laid by M. DOBB on the SCHUMPETER s contribution towards the understanding of macroeconomic models as a political instrument design and ideological. Second, it uses the reading confirms M. BLAUG in the same sense that economic analysis models, hide, without rejecting their premises heuristics. It is used also of a long tradition, revived by K. MARX and not closed in this, which affirms the relevance of politics as the vehicle through which theoretical models, concepts and assumptions are thought of as fed by historical contexts and, at the same time will be part of the consolidation symbolic or not, these same contexts. When such theoretical-methodological aspects are applied to that working hypothesis to explain the study results and understand that the adjustment programmes of the International Monetary Fund and the evidence of their policies have had significant effects, to confirm it, about the current trend financialisation of the world capitalism. If correct, the exposed, lighten and contribute to the understanding of these issues were addressed in the body of work now submitted